Sherpa [videorecording (DVD)] - Peedom, Jennifer (Lionsgate, 2016)
Every year, Western mountain climbers make news ascending Mount Everest. The compelling stories of the Sherpas, the Nepalese guides who risk their lives to provide for their families, have remained a mystery, until now. This chronicles a fateful 2014 expedition and the tragic avalanche that spurred the Sherpas to make a stand for human rights and respect.